Can developing countries "catch up" with weak S&T eco-systems: Some insights from dynamic Asian economies - Venni V. Krishna (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
The post-war era, particularly from the mid-1980s, can be seen as a turning point for various Asian countries. Japanese success in industrialisation based on technology transfer from the industrialised West and evolution of unique endogenous scientific and technological capacities led scholars to conceptualise "late industrialisation" and "catching up" strategies. In a large measure, the "East Asian Miracle" led to some erroneous misconceptions on science, technology, and innovation (STI) policies. Various writings and commentators from Africa, Asia and Latin America advocated to follow the path of East Asian Dragons. These writings begun to assume that countries can build innovation systems or dynamic technological sectors of economy within their respective countries, without paying much attention to building and strengthening science and technology (S&T) eco-systems. There are now clear STI policy signals which point to the significance of building science and technology systems before fully embarking on innovation policies. Drawing on some exemplary cases, this essay will explore the importance of S&T systems in the context of developing countries.
Keywords: 650; Asian Dragons; catch up; developing countries; S&T eco-system